The photoluminescence properties of QWs with asymmetrical step-like InGaN/GaN quantum barriers. (April 2015) - Rajabi, Kamran; Yang, Wei; Li, Ding; He, Juan; Zong, Hua; Ji, Qingbin; Shen, Bingran; Yan, Tongxin; Hu, Xiaodong
Highlights: We applied a low-indium-content to form a step-barrier QW. The PL emission shifted to higher wavelength emissions. The emission mechanism shows a transition between interlayer and QW states. The increasing excitation power increased the recombination lifetime. Abstract: The asymmetrical structures were created by inserting a low-indium-content layer between the QW and barrier to form a step-like quantum barrier (QB) at one side of QW. The optical effects of the inserting layer on QW emission were investigated with low-temperature photoluminescence (PL) and time-resolved PL (TRPL). The inserted layer partially relaxed the strain within QW layer and induced about 25 nm red-shift in the PL emission compared with conventional QW, while the presence of localization centers around QW affected the emission mechanism and increased the radiative decay time. Furthermore, the position of the inserted layer played different roles in the changed structures, and whilst the n-side step-barrier exhibited strong localization in the energy levels of the inserted layer, the p-side step-barrier showed stronger localization center for the QW levels.